The patriarchal framework of social work - Landeros, Martha Gálvez (Seven Editora, 2023)
Social Work, from its origins, has implicitly the purpose of "helping...", an intention recreated in assistance itself. Historically, those who have produced and reproduced, thought, and practiced this profession, are Women. However, more than 60 years after its professionalization in Mexico, atavisms remain that define the very praxis of Social Work. The objective of this article is to make visible symbolic elements that, embedded in the patriarchal ideology, guide the practice of Social Workers in Mexican Public Institutions. The data discussed is the result of qualitative research carried out with 20 Social Workers, as a sample, in the State of Jalisco. Mexico. In-depth interviews and content analysis combined with the interpretive (hermeneutical) method constituted the sequence to produce the data and interpret it. Three dimensions of analysis were established: the past time; self-image and plans-expectations of the profession. The conclusions outline both symbolic elements and those contained in the very praxis of the interviewed professionals. DOI: https://doi.org/10.56238/methofocusinterv1-091